2014
DOI: 10.1111/ppc.12057
|View full text |Cite
|
Sign up to set email alerts
|

The Perceptions of the Ward Atmosphere in Four Jordanian Psychiatric Hospitals From the Perspective of Patients' Relatives

Abstract: By describing their current and ideal treatment environments, participants have provided information that can guide interventions to change the ward atmosphere and thus help foster better patient treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Moreover, previous research has confirmed both the content [45] and criterion validity [46] of the WAS. Additionally, it has been implemented in several cross-cultural contexts [24,29,31,47].…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, previous research has confirmed both the content [45] and criterion validity [46] of the WAS. Additionally, it has been implemented in several cross-cultural contexts [24,29,31,47].…”
Section: Instrumentationmentioning
confidence: 99%
“…Additionally, Jörgensen, Römma, and Rundmo (2009) [23] utilized the Ward Atmosphere Scale and discovered a correlation between the Ward Atmosphere Scale and juvenile satisfaction, while acknowledging more research was necessary. Social climate has been a concept researched in the previous decades [25, [29][30][31], and focused on the perspective within a hospital inpatient unit as opposed to correctional centers.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of family involvement in the treatment of people with serious mental illness has been widely recognized (Al‐Sagarat, Moxham, Curtis, & Crooke, ; Mairs, Lovell, & Keeley, ; Treanor, Lobban, & Barrowclough, ). Patients and their relatives have been encouraged to take a more active role in the planning and delivery of health care in general (Department of Health and Children, ; Partanen, Moring, Nordling, & Bergman, ).…”
mentioning
confidence: 99%
“…Families have also expressed that emphasis in treatment has been put on adverse events and crises caused by patients rather than on methods to prevent them (Jones et al., ). In some cases, nurses may be too strict in controlling patient behavior (Al‐Sagarat et al., ) without respecting the patient's own will (Östman, ). Family members have also experienced a lack of support for patients provided by the nurses (Al‐Sagarat et al., ).…”
mentioning
confidence: 99%
See 1 more Smart Citation